PENGARUH KESESUAIAN BIDANG PENDIDIKAN, KOMPETENSI DAN KEDISPLINAN GURU TERHADAP KINERJA (STUDI) DI SMAN 1 BULULAWANG KABUPATEN MALANG. - Endah Ernayani (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2015)
Performance in the context of the teaching profession is an activity which includes lesson plans, implementation of learning, and assessment of learning outcomes. While discipline is the operative functions of human resource management is important because the higher the better disciplined performance to be achieved. Each teacher is required to have a certain academic quality. Teachers who have an academic qualification means that a diploma level academic education should be owned by teachers must be in accordance with the type, level, and formal education unit in the assignment of teachers. This study aims to (1) quantify the effect of conformity education on teacher performance (2) measuring the effect of competence on teacher performance (3) to measure the effect of discipline on teacher performance (4) to measure the effect of the suitability of education, competence and kedisiplin simultaneously on teacher performance SMAN 1 Bululawang Malang. This study uses a quantitative approach correlational type of survey. The research subject teachers SMAN 1 Bululawang as many as 30 teachers. Methods of data collection for the independent variable using a questionnaire while the dependent variable using the performance appraisal document. Validity and reliability using Cronbach Alpha formula whereas hypothesis testing using t test and F test data analysis using multiple regression , while for determining the partial value of each independent variable using simple linear regression aided SPSS. The results of the analysis of each variable indicate that: (1) no significant effect suitability field of study on teacher performance SMA Negeri 1 Bululawang, (2) no significant effect on the competence of the performance of teachers in SMA Negeri 1 Bululawang, (3) no significant effect of discipline teachers on teacher performance in SMA Negeri 1 Bululawang. This shows that together suitability field of study, competence and discipline has a significant influence on teacher performance SMA Negeri 1 Bululawang.